2001
DOI: 10.1021/tx0001981
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Induction Dependent Bioactivation of Troglitazone and Troglitazone Quinone In Vivo

Abstract: Troglitazone (TGZ), a 2,4-thiazolidinedione antidiabetic, causes hepatotoxicity in 1.9% of patients. TGZ is an inducer of, and substrate for, hepatic P450 3A. Microsomal metabolism yields a benzoquinone (TGZQ) and reactive intermediates. Kassahun et al. [Kassahun et al. (2001) Chem. Res. Toxicol. 14, 62-70] have trapped the intermediates as thioester, thioether, and disulfide conjugates of glutathione and found five conjugates in rat bile. The thioether was substituted in the chromane moiety. We have investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 31 publications
6
94
1
Order By: Relevance
“…5. This adduct may be the same as ML3 or MET1/2, which was reported to be the major adduct formed in rats or in human hepatocytes, as judged based on the similarity of the MS fragmentation pattern (Tettey et al, 2001;Prabhu et al, 2002). Collectively, the major TGZ-GSH adduct is determined to be 5-glutathionyl-5-[4-(6-hydroxy-2,5,7,8-tetramethylchroman-2-ylmethoxy)benzyl]-thiazolidine-2,4-dione.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…5. This adduct may be the same as ML3 or MET1/2, which was reported to be the major adduct formed in rats or in human hepatocytes, as judged based on the similarity of the MS fragmentation pattern (Tettey et al, 2001;Prabhu et al, 2002). Collectively, the major TGZ-GSH adduct is determined to be 5-glutathionyl-5-[4-(6-hydroxy-2,5,7,8-tetramethylchroman-2-ylmethoxy)benzyl]-thiazolidine-2,4-dione.…”
Section: Discussionmentioning
confidence: 94%
“…Tettey et al (2001) and Prabhu et al (2002) reported a major GSH adduct of TGZ formed in rats (ML3) and in human hepatocytes (MET1/2) with a mass spectral pattern similar to that of M5, but the assignment of the position attached to GSH was different. The structure of M5 proposed by Kassahun et al (2001) resulted from the addition of GSH to an o-quinone methide derivative of TGZ.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…43 Likewise, the quinone M3 was not toxic to cultured rat hepatocytes even at concentrations of 100 mol/L (approximately 50-fold the liver concentration). 67 …”
Section: Troglitazone Pharmacokineticsmentioning
confidence: 99%
“…42,43 However, in susceptible individuals, M3 conceivably could react with proteins, RNA, or DNA to induce liver injury. Also, M3-derived reactive intermediates are covalently bound to microsomal protein and glutathione, 67,161 but the significance of these adducts in the pathogenesis of TGZ-associated hepatoxicity is unknown.…”
Section: Potential Genetic and Acquired Susceptibility To Tgzmentioning
confidence: 99%